Does maximalist footwear lower impact loading during level ground and downhill running? - Chan, Z. Y. S.; Au, I. P. H.; Lau, F. O. Y.; Ching, E. C. K.; Zhang, J. H.; Cheung, R. T. H. (European Journal of Sport Science, 2018)
A new model of running shoes which features an extreme cushioning and an oversized midsole, known as the maximalist (MAX) was launched. This design claims to provide excellent shock absorption, particularly during downhill running. This study sought to assess the effects of MAX on the external impact loading, footstrike pattern, and stride length during level ground and downhill running on an instrumented treadmill. Twenty-seven distance runners completed four 5-minute running trials in the two footwear conditions (MAX and traditional running shoes (TRS)) on a level surface (0%) and downhill (10%-declination). Average and instantaneous loading rates (ILRs), footstrike pattern and stride length were measured during the last minute of each running trial. A 12% greater ILR was observed in downhill running with MAX (p = .045; Cohen`s d = 0.44) as compared to TRS. No significant difference was found in the loading rates (p > .589) and stride length (p = .924) when running on a level surface. Majority of runners maintained the same footstrike pattern in both footwear conditions. Findings of this study suggested that MAX might not reduce the external impact loading in runners during level and downhill treadmill running. Instead, this type of footwear may conceivably increase the external impact loading during downhill treadmill running.